Sleep apnoea in severe aortic stenosis. Issue 1029 (25th March 2011) - Prinz, Christian; Bitter, Thomas; Oldenburg, Olaf; Faber, Lothar; Horstkotte, Dieter; Piper, Cornelia
Abstract : Background: There are as yet no data on the prevalence of sleep apnoea in patients with severe aortic stenosis (AS). Aims: To assess the occurrence, severity and clinical correlates of sleep apnoea in patients with AS. Methods: During a 4-month period in 2010, 67 patients were consecutively included in this study, 42 of which (19 men; mean±SD age 72±9 years) had severe AS (aortic valve opening area ≤1.0 cm 2 ); all were investigated with cardiorespiratory polygraphy. Sleep apnoea was diagnosed if the apnoea–hypopnoea index (AHI) (median (lower quartile, upper quartile)) was ≥5/h. The control group of 25 patients matched for age, body mass index and sex had angiographic exclusion of coronary artery disease, regular left ventricular ejection fraction, and no valve disease. Results: Sleep apnoea was found in 30/42 patients with AS (71%; AHI=23/h (14/h, 36/h)). The severity was significantly greater in patients with severe AS than in the control group (AHI=12/h (8/h, 17/h)) (p<0.01). Half of the patients with sleep apnoea had obstructive sleep apnoea (OSA) (AHI=15/h (9/h, 28/h)), and half had central sleep apnoea (CSA) (AHI=25/h (18/h, 45/h)). New York Heart Association classification and severity of sleep apnoea correlated with η=0.5 (η 2 =0.3). The severity of CSA correlated with pulmonary artery pressure (r=0.7, p<0.01) and pulmonary capillary wedge pressure (r=0.7, p<0.01). Patients with AS and CSA had a lower Pco 2 than those with OSA and those without sleep apnoea (p<0.01). Conclusions: Sleep apnoea is common in patients with severe AS. The severity of CSA correlates with pulmonary hypertension, which may suggest that myocardial adaptation is exhausting.